Biological and antibacterial properties of TiO2 coatings containing Ca/P/Ag by one-step and two-step methods. - Zhang, Lei; Li, Baoe; Zhang, Xianlin; Wang, Donghui; Zhou, Linxi; Li, Haipeng; Liang, Chunyong; Liu, Shimin; Wang, Hongshui (Biomedical Microdevices, 2020)
The porous TiO2 coatings containing Ca/P/Ag were separately prepared on titanium (Ti) surface by one-step (micro-arc oxidation) and two-step methods (micro-arc oxidation and cathodic deposition), and then their surface morphology, composition, biological and antibacterial properties were compared. The results showed that the porous coatings containing Ca/P/Ag achieved by different methods showed similar surface morphology and elemental composition, however, by one-step method, silver existed in the coating as silver phosphate, while in the coatings prepared by two-step method, silver existed as metallic silver. Although both coatings showed excellent antibacterial property (the antimicrobial rate is over 99.9%), the surface coating prepared by one-step method had a more suitable release curve of Ag. In addition, the surface coating prepared by one-step method also presented better biological property, which was due to its enhanced surface roughness and hydrophilicity. Combining with its easy operation and long-term antibacterial property, its prospect for clinical application is more promising.